Розвиток методів статистичної фізики у роботах академіка Юхновського - Мриглод, І. (Праці наукового товариства ім. Шевченка, 2011)
This paper is dedicated to the 85-th birthday of academician Yukhnovskii and has the goal to present a brief analysis of the main methods developed by him in the field of statistical many particle physics. The emphasis is made on the following original approach developed for solving the Bogolyubov `s equations in the form of plasma parameter expansions, new possibilities opened up by the collective variables method, concept of reference system in many particle theories, and nonperturbative version of phase transition theory.